2005
DOI: 10.1021/jp051285a
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Coupled Ruthenium−Polypyridyl Complexes for Efficient Electron Injection in Dye-Sensitized Semiconductor Nanoparticles

Abstract: Dynamics of interfacial electron transfer (ET) in the ruthenium-polypyridyl complex [{bis(2,2'-bpy)-(4-[2-(4'-methyl-2,2'-bipyridinyl-4-yl)vinyl]benzene-1,2-diol)} ruthenium(II) hexafluorophosphate] (Ru-cat)-sensitized TiO(2) nanoparticles has been investigated using femtosecond transient absorption spectroscopy detecting in the visible and near-infrared region. It has been observed that Ru-cat is coupled strongly with the TiO(2) nanoparticles through its pendant catechol moiety. Electron injection has been co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(155 citation statements)
references
References 46 publications
8
147
0
Order By: Relevance
“…[13,14] The absorption bands at 400-550 nm are attributed to the MLCT singlet state for complexes 1 and 2. [5,13] After the addition of TiO 2 nanoparticles, the absorption spectrum (Figure 1c) of 1 becomes broad and redshifted with an appreciable increase in absorbance of the band at 460 nm. Once again, after the addition of TiO 2 nanoparticles, the absorption spectrum of complex 2 (Figure 1d) becomes broad and shifted to a longer wavelength with an appreciable increase in absorbance for both (dp Os !p* bpy and dp Os !p* L ) of the MLCT bands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[13,14] The absorption bands at 400-550 nm are attributed to the MLCT singlet state for complexes 1 and 2. [5,13] After the addition of TiO 2 nanoparticles, the absorption spectrum (Figure 1c) of 1 becomes broad and redshifted with an appreciable increase in absorbance of the band at 460 nm. Once again, after the addition of TiO 2 nanoparticles, the absorption spectrum of complex 2 (Figure 1d) becomes broad and shifted to a longer wavelength with an appreciable increase in absorbance for both (dp Os !p* bpy and dp Os !p* L ) of the MLCT bands.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneous electron injection from the thermalized 3 MLCT states has also been observed and contributes to the multiexponential electron injection. In our earlier investigations [5,6] in which we used ruthenium-polypyridyl photosensitizers, namely, TiO 2 nanoparticles sensitized by [Ru [6] (bpy = 2,2'-bipyridine), we observed only a singleexponential electron injection in TiO 2 CB (CB = conduction band) from photoexcited MLCT states. We also observed that the strong electronic coupling between dye-TiO 2 systems facilitates electron injection from nonthermalized MLCT states.…”
Section: Mlct States In the Osmentioning
confidence: 88%
See 1 more Smart Citation
“…[7][8][9][10][11] This feature is associated with the population dynamics of different metalto-ligand charge-transfer (MLCT) states of the dye complex. Following excitation at the maximum of the absorption band (typically at a wavelength of 530 nm), the dye is initially prepared in the singlet 1 MLCT state.…”
Section: Introductionmentioning
confidence: 99%
“…Second, slight difference of the fluorescence lifetimes implies that most IFET processes should be slow and inefficient. The oxazine 1 molecule lacks effective anchoring groups like carboxylate in metal-polypyridine complexes to covalently bind the dye to the semiconductor (Oregan & Gratzel, 1991;Ramakrishna et al, 2005). These dye molecules randomly selected are anticipated to be physisorbed to the TiO 2 NPs surface or loosely trapped at the NPs interstices.…”
Section: Fluorescence Lifetimesmentioning
confidence: 99%